Beyond the Limits: tRNA Array Units in Mycobacterium Genomes - Morgado, Sergio M. (2018)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Genética Molecular de Microorganismos. Rio de Janeiro, RJ. Brasil.